Análisis del ámbito financiero en la actividad profesional que ejercen los egresados de contaduría pública de la Universidad Antonio Nariño sede Duitama del 2015-2019 (2020)
This research will show us the reality that graduates of Public Accounting from the Antonio Nariño University, Duitama headquarters, period 2015-2019, currently recognize the skills they have when working on issues focused on finance. This article will allow us to visualize the professional profile that accountants play within society, in turn we will learn about professional development and the sense of belonging they have for their career, as well as identify the different work fields that professionals currently perform. For the development of this article, a qualitative and quantitative research was carried out, in which the relationship between their professional training and their job performance was analyzed, inquiring if they consider that the training received by the university has allowed them Act as full professionals and additionally, the aim is to identify the difficulties that graduates present when starting their working life, contributing to the university with the findings that allow them to control their graduates.